Muara Jambi: Status and Existence of Buddhist Legacy Between two Powers - Al Fiqri, Yanuar; Santoso, Firdaus Hadi; Hasibuan, Rizki Ananda (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This article aims to explain the existence of the Muara Jambi temple complex in the course of Indonesian History.As one of the largest Buddhist temple complexes in Southeast Asia, Muara Jambi is not widely known by the Indonesian people. Muara Jambi has only been known as a large number of people as the name of an area without knowing that there are important sites in the course of ancient Indonesian history in it. The temple heritage that has been more widely known on the island of Java and is used as the main historical tourist destination for the relics of the Hindu and Buddhist periods, the lack of writing and research on Muara Jambi is one of the main causes of people's ignorance about the Muara Jambi temple complex. One of them is about its status and existence in the history of the kingdoms in Sumatra, which eventually led to two major kingdoms, namely the Malay and Srivijaya Kingdoms.